POTENSI GASTRONOMI WISATA DALAM PEMAJUAN KEBUDAYAAN DI KOTA PONTIANAK - Dina Karlina; Khairunnisa; Tiza Yaniza (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
This study aims to determine and analyze whether tourism gastronomy has the potential to increase cultural advancement in Pontianak City. Regarding the promotion of culture, with the existence of tourism gastronomy, how can this show the role of the food itself, especially traditional food in advancing culture in an area, namely Pontianak City. In the perspective of promoting culture based on Law Number 5 of 2017 concerning the Advancement of Culture, we can examine whether tourism gastronomy which focuses on the traditional food of Pontianak City, especially cakes, can be one of the objects of cultural promotion. The method used in this study is a normative-empirical legal research method by examining the correlation between tourism gastronomy and cultural promotion as well as open interviews with the Pontianak City Youth, Sports and Tourism Office (DISPORAPAR), the Pontianak City Cultural Value Preservation Center (BPNB), the Education Office and Culture (DISDIKBUD) Pontianak City, Pontianak City PKK Mobilizing Team. The results of the study indicate that the potential of tourism gastronomy has good and good prospects in advancing culture in the city of Pontianak. However, in its implementation, tourism gastronomy which focuses on the traditional food of Pontianak City, especially traditional cakes, needs further study and also a wider introduction to the people of Pontianak City. Based on the Decree of the Mayor of Pontianak Number 202 / DISDIKBUD / 2021 which stipulates how many intangible cultural heritages of Pontianak City there are 8 (eight) cultural heritages and there are 4 (four) traditional foods.